Comparison of risk of neurovascular and cardiovascular side effects between tiotropium and other anticholinergic agents - Alzayer, R.; Hughes, Jeffery; Parsons, Richard; Lee, Ya Ping (Radcliffe Medical Press Ltd., 2010)
Aim The aim of this study was to examine the risk of cardiovascular diseases among users of both inhaled (ipratropium bromide or tiotropium bromide) and oral (oxybutynin and propantheline, solifenacin, tolterodine) anticholinergics. Method A retrospective study was undertaken on data obtained from the Food and Drug Administration (FDA) from subjects who had received either an inhaled or oral form of an anticholinergic drug and experienced some side effect during the period from 1988 to 2009. The recorded data included: patien's age, sex, list of drugs and side effects. Side effect rates for the anticholinergic drugs were compared using univariate (Chi-square) and multivariate (logistic regression) methods.Results The files from the FDA held data for 36 491 different subjects, of whom 2610 (7.15%) experienced a cardiovascular or neurovascular side effect. Subjects were classified as taking the oral (45%) or inhaled (55%) class of the drug, with only 109 subjects (0.3%) taking drugs in both forms.Side effect rates differed between anticholinergic drugs. Stroke and hypertension were significantly more common for subjects taking oral anticholinergic drug compared with tiotropium, while other reported vascular side effects (cardiac ischaemia or arrhythmias cardiac failure, cardiac arrest) tended to be more commonly associated with the use of inhaled anticholingerics. These differences persisted after adjustment for age and gender. Conclusion This observational study of recorded side effects showed that, except for stroke and hypertension, patients who were treated with an inhaled anticholinergic drug appeared to be at higher risk of developing neurovascular or cardiovascular side effects, than those treated with an oral drug. However, physicians should also be aware that oral anticholinergic drugs may have similar adverse impacts on health. Further studies on the association between anticholinergic drugs and cardiovascular and neurovascular side effects are recommended.